Optimal Control of the Dynamics of the Spread of Covid-19 With Quarantine and Vaccination : Kontrol Optimal Dinamika Penyebaran Covid-19 Dengan Karantina Dan Vaksinasi - Sulma, Sulma; Nisardi, Muhammad Rifki; Suriani, Suriani; Hukmah, Hukmah; Harianto, Harianto; Firmayasari, Dian (Jurnal Matematika, Statistika dan Komputasi, 2023)
Vaccination and quarantine are effective ways to control the spread of disease. Vaccination helps susceptible individuals to boost immunity. Additionally, quarantine helps reduce interactions which will reduce the infection rate. This study proposed the SEIR mathematical model to describe the dynamics of the spread of COVID-19 by providing control in the form of vaccination and quarantine. Based on Pontryagin's minimum principle, the optimal system for optimal control problems is derived and solved numerically using the Fourth Order Runge-Kutta scheme with the Forward-Backward Sweep approach. A numerical simulation of the optimal problem showed that the spread of disease is eradicated more quickly by vaccination and quarantine. Vaccination in large numbers is needed earlier if the rate of contact transmission is high enough. The provision of quarantine control is required from the beginning until no longer to be applied. A large proportion of quarantine at the beginning of time can suppress the spread of disease in the population.